2015
DOI: 10.1038/srep13144
|View full text |Cite
|
Sign up to set email alerts
|

DBC1/CCAR2 is involved in the stabilization of androgen receptor and the progression of osteosarcoma

Abstract: Deleted in breast cancer 1 (DBC1/CCAR2) is a protein of interest because of its diverse roles in tumorigenesis and its possible role as an androgen receptor (AR) co-activator. However, there are limited studies on the role of DBC1 in osteosarcoma. Therefore, we investigated the role of DBC1 and AR and their relationship in osteosarcoma. Immunohistochemical expression of DBC1 and AR was significantly associated with higher clinical stage and higher histologic grade, and predicted shorter survival. Especially, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…Both CDK11 and AR expression showed adverse predictive value for osteosarcoma patients in disease free survival rates. Consistent with these results, while this manuscript was in preparation, another study also demonstrated that AR expression is abundant osteosarcoma and AR is an independent prognostic indicator of overall survival and relapse-free survival in patients33. The prognostic value of AR has also been reported in prostate cancer.…”
Section: Discussionsupporting
confidence: 77%
“…Both CDK11 and AR expression showed adverse predictive value for osteosarcoma patients in disease free survival rates. Consistent with these results, while this manuscript was in preparation, another study also demonstrated that AR expression is abundant osteosarcoma and AR is an independent prognostic indicator of overall survival and relapse-free survival in patients33. The prognostic value of AR has also been reported in prostate cancer.…”
Section: Discussionsupporting
confidence: 77%
“…There have been many studies on DBC1 in human malignant tumors demonstrating its function in breast cancer . Previous studies have shown the nuclear expression of DBC1 is positively related to clinicopathological factors and poor prognosis in patients with breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Originally named DBC1 by mistake because its gene maps to a region of chromosome 8 that was found homozygously deleted in breast cancers, 1 CCAR2 was instead upregulated in many types of tumors. 1 These findings, together with the fact that CCAR2 loss in vitro prevents cancer cells growth 6, 7 suggested for this protein a role of tumor promoter. On the other hand, CCAR2-knockout mice are tumor prone 8 and, intriguingly, in some cancer patients, CCAR2 down-regulation is associated with poor prognosis, 1 suggesting that it acts as tumor suppressor.…”
mentioning
confidence: 99%